The economic burden of health expenditure on diabetes mellitus among urban poor: a cross sectional study - Rani Javalkar, Sandhya (International Journal Of Community Medicine And Public Health, 2019)
Background: Diabetes mellitus (DM) is a chronic metabolic disease that arises when the pancreas does not produce enough insulin or when the body cannot effectively use insulin. Diabetes is a costly disease because of its chronic nature, the severity of its complications and the means required to control them. The objective of the study was to estimate the expenditure on health care by patients suffering from diabetes mellitus. Methods: A community based cross sectional study was conducted among 189 diabetes mellitus patients in the urban area, Mangalore taluk over a period of 6 months. Data collected by personal interview method, questionnaire was developed to collect the appropriate information on socio demographic details, direct costs and indirect cost in health care for diabetes. Data entry was done in MS Excel and analyzed using SPSS v 16.0. Results: The mean duration of diabetes mellitus 3.93±2.0 years with majority of them had associated co-morbidities 54% and complications 28%. The total expenditure on diabetes is 912 INR per visit, the direct cost of healthcare for diabetic individuals was 553 INR, and indirect expenditure was 359 INR. The average time lost on each visit- 2.6 hours which included travel time, waiting period and consultation. Conclusions: This study shows that the economic burden of diabetes mellitus and its complications are very high and increasingly affecting the lives of urban poor.